En Route to New Therapeutic Options for Iron Overload Diseases: Matriptase‐2 as a Target for Kunitz‐Type Inhibitors. (16th February 2016) - Beckmann, Anna‐Madeleine; Maurer, Eva; Lülsdorff, Verena; Wilms, Annika; Furtmann, Norbert; Bajorath, Jürgen; Gütschow, Michael; Stirnberg, Marit
Abstract: The cell‐surface serine protease matriptase‐2 is a critical stimulator of iron absorption by negatively regulating hepcidin, the key hormone of iron homeostasis. Thus, it has attracted much attention as a target in primary and secondary iron overload diseases. Here, we have characterised Kunitz‐type inhibitors hepatocyte growth factor activator inhibitor 1 (HAI‐1) and HAI‐2 as powerful, slow‐binding matriptase‐2 inhibitors. The binding modes of the matriptase‐2–HAI complexes were suggested by molecular modelling. Different assays, including cell‐free and cell‐based measurements of matriptase‐2 activity, determination of inhibition constants and evaluation of matriptase‐2 inhibition by analysis of downstream effects in human liver cells, demonstrated that matriptase‐2 is an excellent target for Kunitz inhibitors. In particular, HAI‐2 is considered a promising scaffold for the design of potent and selective matriptase‐2 inhibitors. Abstract : High affinity Kunitz‐type matriptase‐2 inhibitors : Kunitz‐type inhibitors revealed slow‐binding inhibition of matriptase‐2. HAI‐1 and HAI‐2 were extensively characterised, both for their enzyme inhibitory effects and for downstream cellular consequences. HAI‐2 provides an excellent scaffold for matriptase‐2 inhibitor design.